(untitled) (KONFERENSIYA, 2025)
This article examines how artificial intelligence has affected contemporary translation techniques, emphasising the development of neural machine translation and AI-assisted workflows. According to the study, AI greatly improves accessibility, terminology consistency, and translation speed. However, it also identifies key limitations, particularly in handling cultural nuances, figurative language, and context-dependent meanings. The findings emphasize that AI cannot fully replace human translators but instead functions as a supportive tool that reshapes their roles toward editing, quality control, and decision-making. The article concludes that the future of translation lies in effective human–AI collaboration